Curious George goes to a chocolate factory - Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977.; Vipah Interactive (Boston : Houghton Mifflin, 1998)
George's curiosity causes a problem at the chocolate factory, but his quick thinking and speedy action on the assembly line help save the candies.
Preschool
AD 440
Accelerated Reader AR
Keywords: Candy -- Juvenile fiction; Chocolate -- Juvenile fiction; Monkeys -- Juvenile fiction